ショウワキチ デ カンソク サレタ タイキ エアロゾル チュウ ノ キンゾク セイブン オヨビ タンソ セイブン ノ キセツ ヘンドウ - 小林, 拓; コバヤシ, ヒロシ; 原, 圭一郎; ハラ, ケイイチロウ; 塩原, 匡貴; シオバラ, マサタカ; 山内, 恭; ヤマノウチ, タカシ; 長田, 和雄; オサダ, カズオ; 太田, 幸雄; オオタ, サチオ; et al. (2010)
P(論文) 南極大気中のエアゾロルの季節変動や人為起源エアロゾルの長距離輸送の影響を調べるために,昭和基地において大気エアロゾルを捕集し分析した.測定した化学種は,元素状炭素および有機性炭素,金属成分としてAl,V,Cr,Mn,Fe,Co,Ni,Zn,そしてPbである.元素状炭素の濃度は4-6月にかけて相対的に低く,3月,10月そして11月に高かった.Al,V,Co,Ni,Pbの濃度は検出限界以下であることが多かった.V,Cr,Fe,Co,Ni,Zn,Pbの濃度は8-10月に突出した最高濃度を記録した.人間活動による南極大気中のエアロゾルの組成への影響を評価するため,各金属成分の濃縮係数を計算した.濃縮係数はブリザードが観測された期間に高くなる傾向を示したことから,低気圧擾乱に伴い人為起源エアロゾルを含む気塊が南極大陸まで輸送された可能性が考えられる. Antarctic aerosols collected at Syowa Station in 2001 were analyzed to investigate their seasonal variations and long-range transport of anthropogenic aerosols. The measured chemical species were elemental carbon and organic carbon, and metals such as Al, V, Cr, Mn, Fe, Co, Ni, Zn and Pb. Concentration of elemental carbon was relatively low in April-June and was high in March, October and November. The concentrations of Al, V, Co, Ni and Pb were sometimes lower than the detection limits. Spikes of the highest concentrations of V, Cr, Fe, Co, Ni, Zn and Pb were recorded in August-October. The enrichment factors were high during blizzards. This indicates that air masses containing anthropogenic aerosols were transported to Antarctica by low-pressure system perturbation. departmental bulletin paper